Link adaptation for Ka band low Earth orbit Earth Observation systems: A realistic performance assessment - Toptsidis, Nikolaos; Arapoglou, Pantelis-Daniel; Bertinelli, Massimo (International journal of satellite communications and networking, 2012)
SUMMARY In this paper, a proposal is sketched for realizing high data rate downlinks in next‐generation Ka band low Earth orbit (LEO) Earth Observation (EO) systems. The work aims at realistically assessing the throughput advantage stemming from link adaptation strategies—embraced by most wireless and satellite communication standards—compared with non‐adaptive transmission, which is the approach followed in conventional X band EO systems. The transmission strategies examined include constant, (static and dynamic) variable, and adaptive flavors of coding and modulation, each representing a different performance/system complexity trade‐off. Practicality is pursued to the extent possible by incorporating state‐of‐the‐art orbital, ground station, spacecraft, propagation, physical layer, and system implementation characteristics. The results manifest that under particular conditions, link adaptation offers throughput improvements of up to 100% against non‐adaptive transmission schemes in Ka band LEO EO systems. Copyright © 2012 John Wiley & Sons, Ltd. In this paper, a proposal is sketched for realizing high data rate downlinks in next‐generation Ka band low Earth orbit Earth Observation (EO) systems. The work aims at realistically assessing the throughput advantage stemming from link adaptation strategies compared with non‐adaptive transmission, which is the approach followed in conventional X band EO systems. The transmission strategies examined include constant, (static and dynamic) variable, and adaptive flavors of coding and modulation, each representing a different performance/system complexity trade‐off.